Profitability of Mass Customization in Electrical Motor Manufacturing : Does Customization Improve Product Level Profitability - Helanen, Ville (My University, 2023)
The current market environment forces manufacturing companies to produce such customized products that are at the same time relatively cheap and finished with top quality to respond demanding requirements of customers. The concept of mass customization has been presented as a solution that offers economies of scale while producing customer tailored products. The aim of this research is to review the impact of mass customization on product level profitability in complex manufacturing environment. The theoretical framework is constructed on the main themes of mass customization, cost accounting, and product profitability analysis. All these mentioned topic areas are reviewed from the viewpoint of a manufacturing company that produces large variety of customized products with different order fulfillment methods. The research problem is divided into two separate questions of evaluating available product costing systems in complex manufacturing environment, and seeking evidence if mass customization is profitable in the case company that for this research is made as an assignment. Based on previous research, financial effects of mass customization are not sufficiently studied through empirical research. Furthermore, related research focuses mostly on product configurations and modules, and their effect on operative and technical development instead of financial measures. The empirical section of this research is conducted as a quantitative single-case study that aims to seek evidence if mass customization of electric motors is profitable for the case company. Operative data is collected from the case company’s ERP-system, and it is combined with financial information. This constructed data set is used for performing statistical analysis similar to methods that are applied in econometrics. The collected data set consists of 3900 statistical units thereby constructing a representative sample from the population. The findings show that mass customization is profitable for the case company when customization is measured through customer selected and otherwise optional variant codes, and by comparing profitability levels in between of different engineering groups. As a results, it was discovered that more customized statistical units were seen to be more profitable than those less customized units. This research contributes filling the recognized research gap of lacking empirical studies related to financial effects of mass customization. In addition, it also presents important information for the case company regarding of how different variant codes and engineering groups affect product level profitability in their manufacturing operations. Furthermore, the presented statistical method offers possibility to analyze and estimate how different product features influence product profitability levels based on statistical methods commonly used in econometrics. Therefore, this research can be seen to have central managerial and practical implications within management accounting practices in manufacturing environments.

Kiristyvä kilpailutilanne markkinoilla sekä vaatimukset räätälöidyistä tuotteista ajavat yrityksiä tarjoamaan asiakaskohtaisia tuotteita saavuttaakseen kilpailuetua muihin kilpailijoihin nähden. Joustavan tuotevalikoiman lisäksi, asiakkaat odottavat samanaikaisesti edullisia hintoja, nopeita toimitusaikoja sekä hyvää laatua tuotteilta. Massakustomoinnin on esitetty tarjoavan mahdollisuuden hyödyntää suuruuden ekonomiaa samalla tarjoten asiakaskohtaisesti valmistettuja tuotteita, jotka täyttävät asiakkaiden erityiset vaatimukset. Tämän tutkimus tarkastelee massakustomoinnin vaikutusta tuotekohtaiseen kannattavuuteen korkean teknologian teollisuusympäristössä. Tutkimuksessa esitetty teoreettinen viitekehys muodostuu massakustomoinnin, kustannuslaskennan sekä kannattavuusanalyysin aihealueista, joita tarkastellaan erityisesti valmistavan tuotannon näkökulmasta. Tutkimuksen tavoitteena on luoda eheä kokonaisuus yhdistäen näitä mainittuja tutkimusaiheita sekä konkretisoida kustomoinnin taloudellisia vaikutuksia empiirisen tutkimuksen avulla. Tutkielman tutkimusongelma on jaettu kahteen erilliseen tutkimuskysymykseen. Ensimmäinen tutkimuskysymys tarkastelee kustannuslaskennan mahdollisuuksia tuotekustannusten määrittämiseksi ympäristössä, jossa tuotteiden määrä on suuri sekä valmistus monivaiheista. Toinen tutkimuskysymyksistä käsittelee massakustomoinnin vaikutusta kannattavuuteen kohdeyrityksessä. Aikaisempi tutkimus tunnistaa puutteet aikaisemmassa empiirisessä tutkimuksessa liittyen massakustomoinnin taloudelliseen vaikutuksiin sen keskittyessä yleisesti kustomoinnin operatiiviseen järjestämiseen sekä kehittämiseen tuotekonfigurointien ja -moduulien avulla. Tämän tutkielman empiirinen tutkimus on muodostettu hyödyntäen kvantitatiivista yksittäistapaustutkimusta, jonka tarkoituksena on tutkia tilastollisia menetelmiä hyödyntäen, miten massakustomointi vaikuttaa tuotekannattavuuteen kohdeyrityksen yhdessä tuote- ja kokokategoriassa. Aineisto on kerätty kohdeyrityksen toiminnanohjausjärjestelmästä sekä taloudellisista raporteista, joista on muodostettu yhtenäinen havaintoaineisto. Koottu havaintoaineisto muodostuu yhteensä 3900 havaintoyksiköstä, joiden voidaan nähdä kuvastavan yleistä tilannetta valitussa tapauksessa. Tulokset osoittavat, että massakustomointi parantaa keskimäärin kohdeyrityksen tuotteiden kannattavuutta, kun kustomoinnin mittana käytetään asiakkaiden valitsemien tuoteoptioiden määrää sekä insinööriprosessin muotoa. Tutkielma osallistuu tunnistetun tutkimusaukon täyttämiseen esittämällä empiirisiä tuloksia kustomoinnin taloudellisista vaikutuksista. Esitelty tilastollinen menetelmä esittää tavan yhdistää kustannuslaskentaa, kannattavuuden analysointia sekä tilastollisia menetelmiä johdon laskentatoimen menetelminä myös muilla massakustomointia hyödyntävillä teollisuudenaloilla lisäten tutkielman hyödyntämisen mahdollisuutta käytännön sekä liikkeenjohdon keinona.
Keywords: mass customisation; manufacturing industry; cost accounting; profitability; statistical methods; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management